Adiabatic quantum-flux-parametron cell library designed using a 10 kA cm−2 niobium fabrication process. (4th January 2017) - Takeuchi, Naoki; Nagasawa, Shuichi; China, Fumihiro; Ando, Takumi; Hidaka, Mutsuo; Yamanashi, Yuki; Yoshikawa, Nobuyuki
Abstract: Adiabatic quantum-flux-parametron (AQFP) logic is an energy-efficient superconductor logic with zero static power consumption and very small switching energy. In this paper, we report a new AQFP cell library designed using the AIST 10 kA cm −2 Nb high-speed standard process (HSTP), which is a high-critical-current–density version of the AIST 2.5 kA cm −2 Nb standard process (STP2). Since the intrinsic damping of the Josephson junction (JJ) of HSTP is relatively strong, shunt resistors for JJs were removed and the energy efficiency improved significantly. Also, excitation transformers in the new cells were redesigned so that the cells can operate in a four-phase excitation mode. We described the detail of HSTP and the AQFP cell library designed using HSTP, and showed experimental results of cell test circuits.